Overexposed other-initiated repair in Mandarin conversation - Yu, Guodong; Zhang, Yaomin (East Asian Pragmatics, 2024)
When the non-trouble-source speaker initiates and even repairs the repairable, s/he might extend the other-initiation or other-correction segment by rejecting or commenting on the trouble source, thus overexposing the trouble source. This study investigates the overexposed other-initiated repair in Mandarin talk-in-interaction. Overexposed other-initiated repairs in Mandarin are executed in a boldfaced manner for a certain interactional reason, which the current research explores from the conversation analytic perspective. Repairables in the current study fall into either error-based or non-error-based ones. Furthermore, the repairables are taken by the interactants as either a common-sense blunder or a moral blunder. In addition, other overexposures reveal the nuanced relation between interactants and their respective epistemic stance in the local interactional environment